A comparative study of the value of amide proton transfer-weighted imaging and diffusion kurtosis imaging in the diagnosis and evaluation of breast cancer - Meng, Nan; Wang, Xuejia; Sun, Jing; Han, Dongming; Bai, Yan; Wei, Wei; Wang, Zhe; Jia, Fei; Wang, Kaiyu; Wang, Meiyun (European radiology, 2021)
Objectives To compare the value of amide proton transfer-weighted imaging (APTWI) and diffusion kurtosis imaging (DKI) in differentiating benign and malignant breast lesions and analyze the correlations between the derived parameters and prognostic factors of breast cancer. Methods One hundred thirty-five women underwent breast APTWI and DKI. The magnetization transfer ratio asymmetry (MTRasym (3.5 ppm)), apparent kurtosis coefficient ( K app ), and non-Gaussian diffusion coefficient ( D app ) were calculated according to the histological subtype, grade, and prognostic factors (Ki-67, estrogen receptor (ER), progesterone receptor (PR), human epidermal growth factor receptor-2 (HER-2), lymph node metastasis, and maximum lesion diameter). The differences, efficacy, and correlation between the parameters were determined. Results The K app value was higher and the D app and MTRasym (3.5 ppm) values were lower in the malignant group than in the benign group (all p < 0.001; AUC ( K app ) = 0.913, AUC ( D app ) = 0.910, and AUC (MTRasym (3.5 ppm)) = 0.796). The differences in the AUC between K app and MTRasym (3.5 ppm) and between D app and MTRasym (3.5 ppm) were significant ( p = 0.023, 0.046). K app was moderately correlated with the pathological grade (| r | = 0.724) and mildly correlated with Ki-67 and HER-2 expression (| r | = 0.454, 0.333). D app was moderately correlated with the pathological grade (| r | = 0.648) and mildly correlated with Ki-67 expression (| r | = 0.400). MTRasym (3.5 ppm) was only mildly correlated with the pathological grade (| r | = 0.468). Conclusion DKI is superior to APTWI in differentiating between benign and malignant breast lesions. Each parameter is correlated with some prognostic factors to a certain extent. Key Points • DKI and APTWI provide valuable information regarding lesion characterization. • K app , D app , and MTRasym (3.5 ppm) are valid parameters for the characterization of tissue microstructure. • DKI is superior to APTWI in the study of breast cancer.